ROLE OF CIVIL SOCIETY IN WOMEN’S EMPOWERMENT IN PAKISTAN: A RESEARCH REVIEW - Kamran (International Research Journal of Social Sciences and Humanities, 2022)
Women are the most significant part of our social structure but despite this fact, they usually faced a number of hurdles in their way to avail their rights. Civil society in Pakistan has been playing its role in social, economic and political empowerment of women. Most of government in Pakistan neglected the well-being of the people especially the empowerment of women. But General Parvez Musharraf regime special importance was given to women empowerment. There were many laws enacted for empowering women such as, the establishment of ministry for women development, an ordinance about the immediate release of women from jail, the passing of women protection bill in parliament, the approval of 10 percent quota instead of 5 percent for women in central superior services by the cabinet. A content is descriptive method used to analyses the role of civil society in empowerment of women. This paper also describes the current status of women in our society. The both primary (Interview, observation) and secondary (books, journal, and Newspaper) sources have been used for collecting and evaluating data. Moreover, this paper is attempt to highlight all those factors which are struggle for the empowerment of women, and also discuss the response or reaction which were came from the empowerment of women.